Growth and Morphological Responses of Duckweed to Clonal Fragmentation, Nutrient Availability, and Population Density - Zhang, Li-Min; Jin, Yu; Yao, Si-Mei; Lei, Ning-Fei; Chen, Jin-Song; Zhang, Qian; Yu, Fei-Hai (Frontiers in Plant Science, 2020)
Disturbance frequently fragments connected ramets (asexual individuals) of aquatic clonal plants. Such clonal fragmentation may interact with nutrient availability and individual density to affect growth and morphology of aquatic clonal plants. We grew the widespread floating clonal plant Spirodela polyrhiza (duckweed) under three levels of density (low, medium, or high), two levels of nutrient availability (low or high), and two levels of clonal fragmentation (with or without). Clonal fragmentation and high nutrients increased biomass and ramet number, but decreased leaf width, leaf length, and specific leaf area of S. polyrhiza. Increasing density decreased leaf and root size and increased leaf thickness of individual ramets of S. polyrhiza. The negative effect of density on growth of S. polyrhiza was greater under high than under low nutrient availability. Furthermore, the negative effect of density on total mass and leaf mass of S. polyrhiza was greater with fragmentation than without. Results suggest that clonal fragmentation, nutrient availability and density can interact to affect growth and morphology of clonal floating plants. Competition for nutrients and space, rather for light, may be the mechanisms underlying the reduced growth of clonal floating plants. As clonal fragmentation can increase biomass and ramet production of S. polyrhiza, potentially disturbance cannot be recommended as a measure to control the spread of clonal floating plants.